An Analysis of Speech Acts Classifications in The Students' English Textbook for Senior High School - Murniasih, Luh Putu Elita (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This research is aimed to analyze the speech acts of the instruction and dialogue found in the tenth-grade of senior high school student’s English textbook; published by the Indonesia Ministry of Education and Culture and to explain out the function of the speech acts. The research is classified into qualitative content analysis research. The data were collected from the directions and dialogues in the English textbook; published by Ministry of Education and Culture. Observation are used to collect the data since the research question was to analyze the types of speech acts used in the instruction and the dialogue of the English textbook and to identify the functions of the speech act base on the context. The instruments used in this research are book “Bahasa Inggris untuk SMA/MA/SMK/MAK kelas X”, the researcher as the human instrument, and the data tabulations. The data were analyzed by reducing the data, displaying the data based on the classifications of speech acts and drawing a conclusion. The result of this research was that speech acts found in the instruction and the dialogue of tenth-grade of senior high school student’s English textbook were directives as the highest frequency of speech acts (68.23%), assertive (16.27%), expressive (13.92%), commissive (0.78%), and declarative (0.78%).